2010
DOI: 10.1051/0004-6361/201014057
|View full text |Cite
|
Sign up to set email alerts
|

The reaction between NH3+and CH3COOH: a possible process for the formation of glycine precursors in the interstellar medium

Abstract: Context. The formation of glycine is strongly relevant to our understanding of the interstellar medium and is most accuretely studied computationally. Aims. We carry out a theoretical study of the reactions between the radical cation of ammonia and CH 3 COOH/CH 2 COOH as possible processes leading to glycine derivatives. Methods. The gas-phase reactions were theoretically studied using ab initio methods. We employed the second-order Moller-Plesset level in conjunction with the cc-pVTZ basis set. In addition, t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
21
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(21 citation statements)
references
References 37 publications
0
21
0
Order By: Relevance
“…Accordingly, these molecules may be present in Titan's atmosphere. Although reaction mechanisms responsible for the formation of some of these molecules have been suggested (see, e.g., Blagojevic et al, 2003;Maeda and Ohno, 2006;Largo et al, 2010), the mechanisms are not known; further work is necessary to identify the specific conditions required for formation.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Accordingly, these molecules may be present in Titan's atmosphere. Although reaction mechanisms responsible for the formation of some of these molecules have been suggested (see, e.g., Blagojevic et al, 2003;Maeda and Ohno, 2006;Largo et al, 2010), the mechanisms are not known; further work is necessary to identify the specific conditions required for formation.…”
Section: Discussionmentioning
confidence: 99%
“…Some reaction pathways have been investigated in the context of amino acid synthesis in the interstellar medium. Experiments by Blagojevic et al (2003) showed that reaction of ionized or protonated hydroxylamine with acetic acid or propanoic acid produces glycine or alanine, while theoretical calculations by Largo et al (2010) showed that reaction of NH þ 3 with CH 3 COOH and CH 2 COOH leads to ionized or protonated glycine. Additional experimental and theoretical calculations are needed to determine whether these or similar reaction pathways operate in the PAMPRE chamber.…”
Section: Present In P5co (See Figs 3 and 4)mentioning
confidence: 99%
“…Kuan et al (2003) has claimed the detection of glycine in the ISM which was disputed by Snyder et al (2005). Subsequently, various studies have been made on the formation of glycine and its precursors in the ISM (Largo et al 2010;Hernandez et al 2011). Majumdar et al (2012) have also shown that NH 2 CHCOOH can be formed by fragmentation of glycine with a reaction rate 7.22 × 10 −10 cm 3 s −1 .…”
Section: 3mentioning
confidence: 99%
“…Of the molecules delivered to the early Earth, the amino acids have tremendous chemical, biochemical and biological significance as key building blocks of proteins, enzymes, and peptides. They have implications in biologically important compounds for the origin of life and therefore deserve particular attention (Largo et al 2010;Hughes 2009;Miao et al 2005). Amino acids have been observed in a number of carbonaceous chondrite meteorites of different classes.…”
Section: Introductionmentioning
confidence: 99%
“…Different ion-molecule processes have been invoked as possible sources of glycine precursors. Experimental (Jackson et al 2005a,b) and theoretical (Largo et al 2004(Largo et al , 2008(Largo et al , 2010 studies of the A&A 579, A125 (2015) reactions of ammonia cations with formic and acetic acids and of different neutrals with amines have been carried out. Some of these reactions involve significant barriers, whereas other barrier-free processes leading to precursors of glycine are less favorable than other competing channels.…”
Section: Introductionmentioning
confidence: 99%